Harnessing AI Innovations for Future-Ready Education in Malaysia Vis-à-Vis Thailand, Singapore and South Korea - Johari, Abdullah; Kee Man, Chuah; Erlinda, Mikal; Syahrul Nizam, Junaini (Springer Cham, 2026)
This chapter explores the transformative role of Generative AI technolo-gies in potentially redefining the educational landscape of Malaysia, with compara-tive insights drawn from Thailand, Singapore and South Korea. In the post-COVID-19 era marked by rapid technological change and evolving pedagogical needs, the chapter examines how these nations are integrating AI into their education systems. It critically analyses the impact of AI tools on educators, students and key stake-holders across these countries, highlighting differences in strategy, implementation and outcomes. Special focus is given to the integration of AI in teaching, learning and assessment practices, providing a regional perspective on innovation and inclu-sivity. The chapter also discusses opportunities and challenges faced by Malaysia and its neighbours in adopting AI in classrooms, offering strategic insights for effec-tive and ethical integration. By comparing approaches and outcomes, this chapter provides a roadmap for educators and policymakers to collaboratively steer AI-driven educational reform in Malaysia and beyond. Ultimately, this chapter contributes to the broader discourse on future-ready education in Asia, positioning Malaysia at the forefront of educational innovation in the face of global technological advancements.